On η,γf,g-Contractions in Extended b-Metric Spaces - Jayashree Patil; Basel Hardan; Ahmed A. Hamoud; Amol Bachhav; Homan Emadifar; Afshin Ghanizadeh; Seyyed Ahmad Edalatpanah; Hooshmand Azizi (Advances in Mathematical Physics)
In this paper, we give a concept of η,γf,g-contraction in the setting of expanded b–metric spaces and discuss the existence and uniqueness of a common fixed point. Introduced results generalize well-known fixed point theorems on contraction conditions and in the given spaces.